PENGAWASAN PENGENDALIAN LIMBAH CAIR RUMAH SAKIT DI KOTA PEKANBARU (STUDI KASUS RUMAH SAKIT ANDINI RUMBAI PEKANBARU) - Fitriani, Aidila; Sahuri, Chalid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Supervisory control of hospital sewage in the city of Pekanbaru aims to identify andanalyze the supervisory control of hospital sewage in the city of Pekanbaru. In fact there aremany hospitals that have not complied with such as have no means of wastewater treatmentbut get permission hospital sewage control, also the presence of a hospital that does not havesuch permission. Study of phenomena, the formulation of the problem of this research is howthe supervision and control of hospital sewage in the city of Pekanbaru and the factors thatinfluence the supervision and control of hospital sewage in the city of Pekanbaru. This studyuses the theory of Darwis, Eni Yulinda, Lamun Banthara.This study used a descriptive analysis method. Data collection technique is theobservation, interviews, and library research. Key informants of this study is the BadanIngkungan Hidup in Pekanbaru, the hospital and the community.The results showed that not maximal supervisory control of hospital sewage in thecity of Pekanbaru is carried out by the Badan Lingkungan Hidup in Pekanbaru. It looks thereare still hospitals that do not have control permit process wastewater and waste properly. Aswell as not optimal implementation factors that influence the Supervision and Control ofhospital sewage in the city of Pekanbaru is the lack of qualified human resources and expertsto go into the field so there are still many hospitals that have not done direct monitoring. aswell as the need to hold socialization to the community.Keywords: Liquid waste, supervision and control.